2020
DOI: 10.3390/catal10090994
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodechlorination of Different Chloroaromatic Compounds at Room Temperature and Ambient Pressure—Differences in Reactivity of Cu- and Ni-Based Al Alloys in an Alkaline Aqueous Solution

Abstract: It is well known that the hydrodechlorination (HDC) of chlorinated aromatic contaminants in aqueous effluents enables a significant increase in biodegradability. HDC consumes a low quantity of reactants producing corresponding non-chlorinated and much more biodegradable organic compounds. Two commonly used precious metals free Al alloys (Raney Al-Ni and Devarda’s Al-Cu-Zn) were compared in reductive action in an alkaline aqueous solution. Raney Al-Ni alloy was examined as a universal and extremely effective HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The effective role of copper-based catalysis in hydrodechlorination (HDC) processes applicable for wastes contaminated with low concentrations of polychlorinated pollutants has been described [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158].…”
Section: Cu-based Hydrodehalogenation Of Aromatic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective role of copper-based catalysis in hydrodechlorination (HDC) processes applicable for wastes contaminated with low concentrations of polychlorinated pollutants has been described [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158].…”
Section: Cu-based Hydrodehalogenation Of Aromatic Compoundsmentioning
confidence: 99%
“…Pyrolysis and combustion are often applied to dismantle e-wastes. The incineration of BFRs-containing e-wastes usually produces, however, polybrominated dibenzo-p-di- Partial HDC of polychlorinated benzenes and regioselective HDC of some chlorinated phenols and chlorinated anilines using Devarda's Al-Cu-Zn alloy in an alkaline aqueous solution at room temperature was studied by Weidlich et al [158]. The HDC activity was explained by the galvanic oxidation of Al from Devarda s Al-Cu-Zn alloy in an aqueous 1 wt.% NaOH solution.…”
Section: Cu-catalyzed Hydrodebromination (Hdb) Of Polybrominated Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This alloy contains 50 wt% of Al and 50 wt% of Ni bound in the form of Al 3 Ni and Al 3 Ni 2 . Different bases such as NaOH or KOH [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104], alkali metal carbonates [89,94,95], NaF [100] or some alkaline salts of complexing agents [91,101] were proved for HDH processes. It was observed that Raney Al-Ni alloy is, especially in diluted aq.…”
Section: Utilization Of Raney Al-ni Alloy In Hdh Processesmentioning
confidence: 99%
“…Chlorine containing organic molecules have been widely used in industry as dry cleaning solvents for degreasing, as intermediates for the production of refrigerants [1,2] or for micro structured silicon carbide films in semiconductor production [3]. However, the contamination by chlorinated organic compounds is very hazardous for the environment and causes pollution of underground water, depletion of the ozone layer and threats the human health because of toxicity and carcinogenic effects [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%